Pengembangan Aplikasi Sistem Monitoring Keamanan Berbasis Linux, Menggunakkan CCTV Dan SMS Gateway - Wijayanto, Agung, Fatah Yasin Irsyadi ST, MT (2015)
The development of applications that I created that adds features of the systems previously on the safety monitoring of a room. Development using CCTV (closed-circuit television) CCTV usually just record a location and send pictures or video from the results that have been recorded and then viewed by the user. Then I add features such as motion detection and SMS notifications in case of moving viewing CCTV from the Internet via a web browser. All that serves to CCTV is monitored by remotely notify in case of moving location via SMS at a moment's notice, can be viewed via the web to be able to immediately see what is happening on the site in case something undesirable could know right away. Connect all the software and hardware to run well, and the UMS diperpustakan research in order to obtain the IP addresses so that the laptop can be put online. Equipment needed ranging from hardware is a laptop as a server, a modem for SMS, CCTV for motion detection recording, HP to receive SMS. Software includes Gammu to send SMS when there is motion, zoneminder as the driver on CCTV and to detect motion, mozilla to see the results of moving footage in question, Phpadminbasenya data processing. Application development Linux-based security monitoring system using CCTV and SMS gateway. I developed that have more CCTV in terms of security for monitoring a location. The first feature to add motion detection (modetc) is useful for detecting motion in a location and add a SMS notification when there is motion in a secured location, features both saw record move that caught on CCTV via a web browser. Features that are added will make it easier to secure the location of the remote because it can be connected to the Internet network and in the event of a crime or theft tindakkan on the location can be secured directly on the spot.